Assessment of Sarocladium oryzae Growth Inhibition, the Causal Agent of Rice Sheath Rot Disease, Using Methanol Extract of Binahong Leaves - Endah Yulia; Silviya Rahma Dhiya Syafira; Fitri Widiantini; Wawan Kurniawan (CROPSAVER, 2019)
Sheath rot disease caused by Sarocladium oryzae is an important disease on rice. The pathogen that infects uppermost leaf sheath enclosing to the young panicles can cause yield losses up to 85%. Though the disease is commonly controlled using synthetic fungicides, the use of natural products that safer to the environment have been enormously explored. The research aimed to test growth inhibition of S. oryzae colony using methanol leaf extract of binahong (Anredera cordifolia). The research was carried out from June until December 2017 at the Laboratory of Biotechnology Plant Protection, Department of Plant Pest and Diseases, Faculty of Agriculture, Universitas Padjadjaran. The method used was Randomized Complete Design consisted of six treatments and four replications. The treatments were five concentrations of binahong leaf extract of 0.125%, 0.25%, 0.5%, 1%, 2% and one control treatment. The result showed that binahong leaf extract did not inhibit the growth of S. oryzae. The highest inhibition percentage of 4.55% at 0.25% concentration was considered to be a low inhibition category. Although the colony growth of S. oryzae was not significantly inhibited, the extract caused hyphal abnormalities. This actually shows the antifungal potency of the binahong leaf extract that needed further examination with more adequate methods.Keywords : Anredera cordifolia, botanical pesticide, rice sheath rot